Ecotheology Sustainability and Religions of the World - Hufnagel, Levente (IntechOpen, 2023)
Ecotheology - Sustainability and Religions of the World gives a very interesting overview of the frontiers of scientific research in this important multi- and transdisciplinary area. Its chapters use ecotheological approaches to discuss the multiple aspects of an environmental crisis from almost every segment of our planet. This book will be very useful for everyone - researchers, teachers, students, or others interested in the field - who would like to gain some insights into this aspect of our culture.